Institutional Conscientious Objection to Medical Assistance in Dying in Canada: A Critical Analysis of the Personnel-Based Arguments - Abernethy, Nicholas (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2023)
Debate rages over whether Canadian provincial and territorial governments should allow healthcare institutions to conscientiously object to providing medical assistance in dying (MAiD). This issue is likely to end up in court soon through challenges from patients, clinicians, or advocacy groups such as Dying With Dignity Canada. When it does, one key question for the courts will be whether allowing institutional conscientious objection (ICO) to MAiD respects (i.e., shows due regard for) the consciences of the objecting healthcare institutions, understood as unitary entities. This question has been thoroughly explored elsewhere in the academic literature. However, another key question has been underexplored. Specifically, precedent set by the Supreme Court of Canada’s decision in Loyola High School v. Quebec (Attorney General) suggests that the courts will consider whether allowing ICO to MAiD respects the consciences of the personnel within objecting healthcare institutions. My answer to this question is no, by which I mean that allowing ICO to MAiD shows undue disregard for some consciences and undue regard for others. To justify this answer, I analyze the arguments that hold that allowing ICO in healthcare respects the consciences of the personnel within objecting healthcare institutions. My conclusion is that none of these personnel-based arguments succeed in the case of ICO to MAiD. Some fail because they are wrong about the nature of conscience and complicity. Others fail because they contradict the arguments’ proponents’ positions on conscientious objection by individual healthcare providers. Still others fail because they are internally inconsistent.